2022
DOI: 10.1016/j.cities.2021.103554
|View full text |Cite
|
Sign up to set email alerts
|

Household mobility in food purchasing during COVID-19 lockdown: Evidence from Torino, Italy

Abstract: During the first wave of COVID-19, lockdown restrictions limited people's movements mainly to food purchasing. Using survey data collected in Torino, Italy, from university students, this study analyses the lockdown's impact on the transportation means used for purchasing food compared to the pre-lockdown period. Food store businesses were not limited by the restrictions and people had to purchase food; however, national and local rules limited citizens' movements, potentially leading to a different choices of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The COVID-19 measures imposed several changes to travel behaviour and choice of transport mode during the pandemic ( Zhang et al, 2021 ). The majority of the studies have reported a general decrease in overall daily mobility ( Li et al, 2022 ; Monterde-i-Bort et al, 2022 ), a reduction in public transport ridership ( Abduljabbar et al, 2022 ; Abdullah et al, 2022 ; Zafri et al, 2021 ), and a switch (shift) from shared travel modes towards using private modes ( Abdullah et al, 2020 ; Braut et al, 2022 ; Das et al, 2021 ; Dingil & Esztergár-Kiss, 2021 ; Eisenmann et al, 2021 ; Padmakumar & Patil, 2022 ) and active modes ( Kyriakidis et al, 2023 ; Schaefer et al, 2021 ; Tarasi et al, 2021 ). In many countries like Italy, and Germany, mobility dropped by around 80 % during the pandemic ( Bernhardt, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 measures imposed several changes to travel behaviour and choice of transport mode during the pandemic ( Zhang et al, 2021 ). The majority of the studies have reported a general decrease in overall daily mobility ( Li et al, 2022 ; Monterde-i-Bort et al, 2022 ), a reduction in public transport ridership ( Abduljabbar et al, 2022 ; Abdullah et al, 2022 ; Zafri et al, 2021 ), and a switch (shift) from shared travel modes towards using private modes ( Abdullah et al, 2020 ; Braut et al, 2022 ; Das et al, 2021 ; Dingil & Esztergár-Kiss, 2021 ; Eisenmann et al, 2021 ; Padmakumar & Patil, 2022 ) and active modes ( Kyriakidis et al, 2023 ; Schaefer et al, 2021 ; Tarasi et al, 2021 ). In many countries like Italy, and Germany, mobility dropped by around 80 % during the pandemic ( Bernhardt, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, shifts from shared travel mode towards using private mode and active mobility such as walking and cycling were reported that was mostly due to the negative perception of contagion and the possibility of smart working ( Braut et al, 2022 ; Li et al, 2022 ; Nikiforiadis et al, 2022 ; Nikolaidou et al, 2023 ). For instance, in some cities such as Milan and Madrid, the ridership decreased by 88 % during the pandemic ( Navarrete-Hernandez et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Households, particularly low-income households, have become more sensitive to food prices as a result of price shocks from food supply chain disruptions and income shocks from unemployment ( 24 , 25 ). Self-quarantine and mobility restrictions changed households' choices of transportation means ( 26 ) and prompted them to increase online shopping ( 27 ). Although a few studies have explored the changes in food expenditure and food insecurity in relation to the pandemic ( 8 , 28 ) they are narrower in scope because of the limited time frame, geography, and smaller sample size.…”
Section: Introductionmentioning
confidence: 99%
“…The research indicated the potential for low-frequency work travel but increased car dependency following the pandemic. Using survey data collected in Italy, Braut et al (2022) analyzed the lockdown's impact on the household mobility in food purchasing. The results show that the lockdown moved the preferences of people from public and shared means to foot and private vehicles for food purchasing activity.…”
Section: Literature Reviewmentioning
confidence: 99%